Study of emotional intelligence of a medical university students - Alimbayeva, R.T.; Yesnazarova, L.U.; Lazareva, Ye.A. (KSU Publ., 2018)
This article examines the role of emotional intelligence in the professional work of doctors. The understanding of emotional intelligence in foreign and Russian psychology is presented. The general characteristic of the basic models of emotional intelligence is given. The components included in the structure of emotional intelligence are described. The urgency of this line of research is substantiated. In the study, the percentage of students of a medical university with a low, medium and high level of emotional intelligence development was revealed. Features of the development of empathy, emotional consciousness and self-motivation in these students are described.
Медициналық университет студенттерінің эмоционалдық зердесін зерттеу
Исследование эмоционального интеллекта студентов медицинского университета
Keywords: emotional intelligence; empathy; emotional consciousness; self-motivation